Vocabulary Learning Through Videos: Captions, Advance-Organizer Strategy, and Its Combination for Fifth Grade Students - Siti Nurwulan; Khusaini Khusaini; Syifa Fadhilah Hamid (Journal of Excellence in English Language Education, 2022)
This research describes the use of Videos media for learning vocabulary and has found positive results in improvement students' vocabulary mastery. The purpose of this research is to find out whether there was an improvement in vocabulary mastery at fifth grade of SDN Kutajaya I in Academic Year 2021/2022 after using Videos. The sample used is 30 students. The writer used quantitative methods with pre-experimental design one group pretest and posttest. The writer was conducted a research using pretest, treatments and posttest. The results showed that the use of Videos can improve students' vocabulary learning. The data hypothesis test used the Wilcoxon Signed Ranks Test, and the results were Ha accepted and Ho was rejected. It can be shown that Sig. < (0.05). This means that there is a significant difference between the pre-test and post-test at SDN Kutajaya I. Learning vocabulary by using Videos can make students more interested in the learning activity. In addition, it is not easy to make students feel bored because learning atmosphere is more exciting.